Evaluating the Levels of Mental Health Awareness in Higher Education Institutions - Baiq Anisya Nelahi Purnadya; Nurul Asmaya Fitria Hasanah; Baiq Oriza Januarlinda; Gunawan Gunawan (Indonesian Publication Center, 2026)
Mental health awareness is a crucial issue in the higher education ecosystem, given the high academic, social, and personal pressures experienced by students. This study aims to analyze the level of student awareness of mental health in higher education through a survey titled